The effectiveness and safety of acupuncture for chemotherapy-induced peripheral neuropathy: A systematic review and meta-analysis - Xu, Zhonghang; Wang, Xingbo; Wu, Yuanyu; Wang, Chengbing; Fang, Xuedong (Frontiers in Neurology, 2022)
Objectives: This systematic review and meta-analysis aimed to evaluate the effectiveness and safety of acupuncture on Chemotherapy-Induced Peripheral Neuropathy (CIPN). Methods: We searched for relevant randomized controlled trials (RCTs) in PubMed, Cochrane Library, and Embase databases from their inception to 1 April 2022. We chose the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx) as the primary outcome and the Brief Pain Inventory-Short Form (BPI-SF), the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire‐Core30 (EORTC QLQ-C30), the Numerical Rating Scale (NRS), and adverse events as the secondary outcome. Mean differences (MDs) with 95% confidence intervals (CIs) were performed a meta-analysis using RevMan 5.3 software. Results: A total of eight studies were involved. The results showed that acupuncture was better than other interventions in reducing chemotherapy-induced neurotoxicity and functional disability (random-effect estimates; MD: 3.91; 95% C1: 1.33 6.49; P=0.003). The heterogeneity was apparent (I2=64%). However, there was no statistically significant difference in reducing chemotherapy-induced neurotoxicity and functional disability between acupuncture and sham acupuncture with no heterogeneity (fixed-effect estimates; MD: 1.59; 95% C1: -1.05 4.23; P=0.24; I2=0%). Acupuncture was better than other interventions in reducing the symptom severity in CIPN (random-effect estimates; MD: -1.15; 95% C1: -1.80 -0.50; P=0.001), with no significant heterogeneity (I2=43%). Acupuncture was better in reducing the pain severity and pain interference with patients’ daily function compared to other interventions (fixed-effect estimates; MD: -0.72; 95% C1-0.86 -0.57; P<0.001), no significant heterogeneity (I2=18%). Acupuncture improved quality of life compared to conventional medicine (MD: 10.10; 95% C1: 12.34 17.86, P=0.01). The eight studies included did not report the occurrence of serious adverse events. Conclusions: This meta-analysis suggests that acupuncture may effectively reduce chemotherapy-induced neurotoxicity and functional disability and maybe a safe treatment. And the level of evidence was low. However, extensive sample size studies are needed to confirm this conclusion further. In addition, acupuncture may reduce pain, relieve symptoms of discomfort, and improve the quality of life for patients with CIPN. The level of evidence was moderate. In the future, high-quality RCTs with multicentre and large sample sizes are needed to prove the effectiveness and safety of acupuncture for CIPN.